1993
DOI: 10.1381/096089293765559700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surgically Induced Weight Loss on Asthma in the Morbidly Obese

Abstract: Forty morbidly obese asthmatic patients who underwent gastric restrictive surgery more than 2 years earlier were evaluated to determine the influence of weight loss on asthma outcome. Mean percentage excess weight loss in this group was 68% and body mass index (BMI) fell from a mean of 46 to 30. Following surgery, 90% showed improvement in asthma symptoms. Complete remission of asthma occurred in 48% and a further 12.5% became asthma free on reduced medications dosage. Of those taking daily medications for ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 19 publications
1
53
0
Order By: Relevance
“…26 In adults, a reduction in excessive body weight by medical treatment and surgical procedures has resulted in a reduction of asthma symptoms, medication usage, and severity, and in improvement of lung function, indicating a possible causal relationship. [27][28][29] When considering our results, some possible limitations of this study should be discussed. First, the ISAAC questionnaire used in this study depended on the recall of asthma symptoms by parents.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…26 In adults, a reduction in excessive body weight by medical treatment and surgical procedures has resulted in a reduction of asthma symptoms, medication usage, and severity, and in improvement of lung function, indicating a possible causal relationship. [27][28][29] When considering our results, some possible limitations of this study should be discussed. First, the ISAAC questionnaire used in this study depended on the recall of asthma symptoms by parents.…”
Section: Discussionmentioning
confidence: 94%
“…14,15 Data on the effect of asthma in children with excessive body weight in the 62 (45) 7 (27) 73 (45) 9 (41) *n, Absolute number for the weight or disease group. %, Percent of total weight or disease group; however, because of missing values, data can be lower or higher than calculated.…”
Section: Discussionmentioning
confidence: 99%
“…28 Moreover, several prospective studies of obese asthmatics have shown that weight reduction leads to improved pulmonary function, and reduced severity and frequency of asthma symptoms. [29][30][31][32][33] The evidence of a relationship between obesity and asthma is not conclusive, however. Several studies find a relationship between obesity and asthma only in females, not in males.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a nexus of these two epidemics exists [22], as shown by the recognition from a number of epidemiological studies (although not all studies [22]) that obesity is associated with an increased relative risk of asthma in both adults [21,[23][24][25][26] and children [27][28][29][30]. A more limited body of evidence suggests that obesity may also increase the severity of asthma, as weight loss by various means resulted in improved disease control in several small series [31][32][33][34][35]. However, the present authors are unaware of any studies that have explored the possibility that obesity might influence therapeutic responsiveness either to asthma medications or to the placebo itself.…”
mentioning
confidence: 99%